2020
DOI: 10.1186/s40168-020-0787-2
|View full text |Cite
|
Sign up to set email alerts
|

Linking belowground microbial network changes to different tolerance level towards Verticillium wilt of olive

Abstract: Background: Verticillium wilt of olive (VWO) is caused by the soilborne fungal pathogen Verticillium dahliae. One of the best VWO management measures is the use of tolerant/resistant olive cultivars. Knowledge on the oliveassociated microbiome and its potential relationship with tolerance to biotic constraints is almost null. The aims of this work are (1) to describe the structure, functionality, and co-occurrence interactions of the belowground (root endosphere and rhizosphere) microbial communities of two ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 73 publications
10
66
0
Order By: Relevance
“…When the whole microbial communities are considered, in contrast with previous studies [ 56 , 57 ], no cultivar effect on bacterial and fungal endophytic assemblages was found using both sequencing approaches. However, our result is in agreement with the results of a recent microbiome investigation on the Verticillium -olive pathosystem showing similar root endosphere and rhizosphere microbial communities between susceptible and tolerant cultivars [ 37 ]. In our study, the negligible host cultivar effect on microbiome composition might be explained by the high presence/abundance of Xylella in the orchards surveyed that seems to have overshadowed the effect of host cultivar in shaping endophytic microbial communities.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When the whole microbial communities are considered, in contrast with previous studies [ 56 , 57 ], no cultivar effect on bacterial and fungal endophytic assemblages was found using both sequencing approaches. However, our result is in agreement with the results of a recent microbiome investigation on the Verticillium -olive pathosystem showing similar root endosphere and rhizosphere microbial communities between susceptible and tolerant cultivars [ 37 ]. In our study, the negligible host cultivar effect on microbiome composition might be explained by the high presence/abundance of Xylella in the orchards surveyed that seems to have overshadowed the effect of host cultivar in shaping endophytic microbial communities.…”
Section: Discussionsupporting
confidence: 93%
“…The majority of studies on the olive microbiome based on cultivation-dependent or independent sequencing, independently of Xylella infections, targeted the rhizosphere compartment [ 35 , 36 , 37 , 38 ] while they are limited for endophytes of aboveground tissues. Using 16S rRNA gene amplicon sequencing, Müller et al [ 39 ] found that the bacterial endophyte communities from leaves and boughs of wild and cultivated olives were largely shaped by the plant genotype and correlated with the geographic origin.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive knowledge of the composition, structure, and functioning of the prokaryotic and fungal communities associated with olive roots will enhance our understanding of the health, development, and fitness of this tree crop. Moreover, under the holobiont conceptual framework, innovative perspectives can be foreseen in areas such as breeding for VWO resistance and the development of novel biocontrol tools [13,184]. Earlier, the olive associated microbiota was reported as an important reservoir of microorganism with potential as BCA against VWO [185].…”
Section: The Olive Belowground Microbiota: Yet To Be Fully Uncovered mentioning
confidence: 99%
“…On the other hand, it was not known either what changes, if any, the root endosphere and rhizosphere microbial communities of olive cultivars with different VWO tolerances undergo upon inoculation with V. dahliae. Therefore, the objective of a very recent study aiming to address these questions was to assess whether the belowground microbial communities of cultivars Frantoio (VWO tolerant) and Picual (VWO susceptible) contribute to their differential disease susceptibility level [184]. Comparing the microbial communities of non-inoculated plants of each cultivar, some interesting differences were observed.…”
Section: The Olive Belowground Microbiota: Yet To Be Fully Uncovered mentioning
confidence: 99%
“…The resulting ltered and trimmed sequences were clustered into Operational Taxonomy Units (OTUs) using UPARSE [58] from the SEED2 package and applying the average neighbour algorithm with a similarity cut off of 97%. The OTUs with less than 0.005% of high-quality reads were then ltered to avoid an overestimation of the diversity [59,60].…”
Section: Data Processingmentioning
confidence: 99%